1978
DOI: 10.1111/j.1469-7998.1978.tb03334.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of locomotion of dogs (Canis familiaris) and sheep (Ovis aries)

Abstract: Records have been made of the forces exerted on the ground by dogs and a sheep, in walking, trotting, cantering and slow galloping. Film has been taken simultaneously. The difference between walking and trotting was much less marked for the sheep than for the dogs. Step length and stride length increase as speed increases. They are expressed as functions of the Froude number. The vertical component of the force exerted by a foot on the ground shows two main maxima in walking, except in the case of the fore fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 13 publications
6
107
1
Order By: Relevance
“…In fact, kinematics, ground reaction force determination, or both have been used in a variety of species such as elephants [33][34][35] , cattle 36 , horses [37][38][39][40] , dogs 4,[41][42][43][44][45] , cats 21,[46][47][48][49] , various rodents 3,8,50,51 , birds 4,[52][53][54][55] , and fish 56,57 (this list is by no means exhaustive). In the authors' experience, however, the use of mice is problematic given that mice are not easy to operantly condition to travel along a runway.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, kinematics, ground reaction force determination, or both have been used in a variety of species such as elephants [33][34][35] , cattle 36 , horses [37][38][39][40] , dogs 4,[41][42][43][44][45] , cats 21,[46][47][48][49] , various rodents 3,8,50,51 , birds 4,[52][53][54][55] , and fish 56,57 (this list is by no means exhaustive). In the authors' experience, however, the use of mice is problematic given that mice are not easy to operantly condition to travel along a runway.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the forelimb supports the majority of the body weight, in a variable percentage. In dogs, for instance, the fraction of body weight supported by the front legs varied from 61% in static conditions (Jayes and Alexander, 1978) to 57% in dynamic conditions (Walter and Carrier, 2007). Using simple models, it has been demonstrated that it is beneficial to a galloping system to have the centre of mass closer to the shoulder than to the hips.…”
Section: Centre Of Mass Positionmentioning
confidence: 99%
“…The Journal of Experimental Biology 215 (23) length (Jayes and Alexander, 1978). Moment of inertia and radius of gyration of the body and of the long bones have been also calculated.…”
Section: Data Collectionmentioning
confidence: 99%
“…Rather than being raised in the first half of the stance phase, it is lowered and the body moves as a wave, often with minimal oscillation in those breeds of dogs that are used to trotting for long periods of time [6]. Here potential energy is converted into elastic energy and stored upon impact with the ground by passive stretching of tendons and muscles, to be released later on in the stance phase.…”
Section: Open Access Research Articlementioning
confidence: 99%